2021
DOI: 10.1007/s10899-021-10091-6
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Among Finnish 14–16-Year-Old Adolescents Before (2008–2009), During (2010–2011), and After (2013–2017) Setting the Legal Age Limit of 18 for Gambling and the Role of Socio-Economic Status

Abstract: Legislation prohibiting minors from engaging in gambling is a gambling policy measure set to protect adolescents from the harmful effects of gambling. The Finnish gambling system is based on a state monopoly, regulated by the Lotteries Act. After an amendment to the Lotteries Act, the new minimum legal gambling age was raised to 18 years old between 2010 and 2011. The main purpose of this study was to discover how the amendment to the act altered adolescents’ gambling (14–16-year-olds) and to examine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…However, other possibilities (e.g., the increasing popularity and social acceptability of sport gambling, especially following the introduction of daily fantasy sports in Connecticut in 2017 and their promotion through frequent advertisements) warrant consideration. The observed gambling prevalence estimate is lower than estimates based on national telephone-based surveys (44.3% to 68%) and in the low range of what was has been reported among students in schoolbased surveys (24.4% to 86%) and convenience samples (22.5% to 47.4%), although changes over time in the prevalence of adolescent gambling during the early part of the second decade of this millennium should also be considered (48,49). Although half of the adolescents who have been gambled last year reported doing it only 1 or 2 times, 12.7% of gambling adolescents reported gambling 20 or more times, with 8.4% reporting more than 40 times.…”
Section: Discussionmentioning
confidence: 52%
“…However, other possibilities (e.g., the increasing popularity and social acceptability of sport gambling, especially following the introduction of daily fantasy sports in Connecticut in 2017 and their promotion through frequent advertisements) warrant consideration. The observed gambling prevalence estimate is lower than estimates based on national telephone-based surveys (44.3% to 68%) and in the low range of what was has been reported among students in schoolbased surveys (24.4% to 86%) and convenience samples (22.5% to 47.4%), although changes over time in the prevalence of adolescent gambling during the early part of the second decade of this millennium should also be considered (48,49). Although half of the adolescents who have been gambled last year reported doing it only 1 or 2 times, 12.7% of gambling adolescents reported gambling 20 or more times, with 8.4% reporting more than 40 times.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, Langham et al (2016) demonstrated the impact of financial harm by delineating it as a continuum, capable of manifesting as both an immediate crisis and a lasting legacy. Lack of FWB consequences identified in the literature includes trouble in meeting daily ends (e.g., reduced disposable income, not being able to cover basic needs or payday loans), lack of financial resilience (e.g., unable to take small financial shocks like buying a wedding gift), lack of future financial security (e.g., asset losses), and lesser financial choices (e.g., homelessness) (Hilbrecht et al, 2020(Hilbrecht et al, , 2020Langham et al, 2016;Latvala et al, 2022).…”
Section: Gambling and Consequences Of Financial Harmmentioning
confidence: 99%
“…Namun berbeda dengan laporan penelitian sebelumnya bahwa remaja pria yang berjudi telah dilaporkan terus berkurang bahkan umumnya memiliki sikap negatif terhadap perjudian yang dianggap berbahaya, terlalu lazim, dan tidak ada aturan yang jelas (Delfabbro dan King, 2021). Namun, laporan terbaru mengenai aturan yang melarang anak di bawah umur yang terlibat dalam perjudian ditetapkan untuk melindungi remaja dari efek berbahaya, hal ini mempengaruhi penurunan perjudian yang dilakukan kelompok remaja (Latvala et al, 2022). Hal tersebut menjadi kesejangan diantaranya bagi negara yang belum memiliki aturan yang tertuang dalam perundang-undangan.…”
Section: Pendahuluanunclassified